Status of rat infestation and recent control strategies in oil palm plantations in Peninsular Malaysia - M. N., Hafidzi; M. K., Saayon (Universiti Putra Malaysia Press, 2001)
A survey was carried out to establish the status of rat infestation and recent rat control practices in oil palm plantations in Peninsular Malaysia. Rattus tiomanicus (Miller) constitutes a major rat species (68 %), followed by Rattus argentiventer (Robinson and Kloss), (46%) and Rattus rattus diardii (L.), (28%). Although 75% of estates did not consider rats as a serious problem, the damage estimated ranges from 0.01 to 0.1 t/ha. The barn owl Tyto alba (Scopoli) is now an important rat control component in oil palm i.e. 82% of estates that participated in the survey. In some estates (21.4%) control is achieved entirely with T. alba, without baiting. In most estates (60.7%) baiting was done in combination with T. alba, whereby the latter reduced baiting cost from RM2.64 to RM30/ha/year.